Feasibility of The Special Index for Handling Stunting (IKPS) as an Indicator of Government Performance in Stunting Management in Indonesia - Simarmata, Yuliana Wisna; Fitriati, Rachma (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Background: Stunting is a crucial issue in the 2024-2029 presidential election, as its resolution is key to achieving a Golden Indonesia vision by 2045. Addressing stunting has become a primary agenda for the Indonesian government, as outlined in the 2020-2024 National Medium-Term Development Plan. The President has instructedStatistics Indonesia to develop a measurement for stunting, namely IKPS. No studies have evaluated the suitability of IKPS as a performance measurement tool. This study aimed to assess the feasibility of IKPS as a government performance indicator in addressing stunting in Indonesia.Method: This Cross-sectional study utilized secondary data from IKPS. Stunting prevalence data for 2018 and 2019 were sourced from the combined Indonesian Toddler Nutritional Status Study and the 2019 National Socioeconomic Survey. Data analysis included descriptive statistics, correlation tests, simple regression analysis, and quadrant analysis to measure relationships and effects between the variables.Result: No significant relationship was found between IKPS and stunting prevalence (r=-0.092, p-value=0.593), though a strong and significant correlation was observed between changes in IKPS and stunting prevalence (r=-0.467, p=0.005).Conclusion: The relationship pattern was unexpected, showing a negative linear association in which increased IKPS did not effectively reduce stunting prevalence. These findings highlight the need for a valid IKPS for program planning, evaluation, and decision-making and suggest further research on IKPS construction methodology.